Sastra Wulang dari Abad XIX: Serat Candrarini Suatu Kajian Budaya - Wahjono, Parwatri (UI Scholars Hub, 2004)
The Book of Candrarini is an ethic didactical book for women in polygamist system, for the eternity of her marriage. It was a disgrace that a woman divorced. This book was the masterpiece of it’s era, written in 1860 in the glory of feodalism in Surakarta, where the authority, high officials and the very peoples did polygamy. That is why His Majesty Paku Buwana IX had Ranggawarsita to write an ethic didactic for women, with the five wives of Arjuna as the model: three princesses and two daughters of priest with very nice performance and gentle behaviour. They lived in harmony, devoted to their husband. The ethic didactic was a catharsis for women in concubine. This research observes Candrarini from its own internal aspects as literary, religious, historical, political, sociological and psychological aspect. The result is : Beauty of a woman does not lie so much in her external appearance as in her internal virtues like modesty, chastity, compassion, service and refined manners. That is the way to save and preserve the eternity of marriage’s life. The ethic is always up to date, everlasting, eternal.